KAJIAN PRAGMATIK ILOKUSI DALAM PERCAKAPAN ORANG TUA DAN ANAK - Hapsari, Diah Arum; Sholikhah, Riza Mar’atus; Anggraini, Nabila Syifa (Hasta Wiyata, 2021)
Communication that occurs between parents and children can be studied in pragmatic studies. This study aims to describe the types of illocutionary speech acts contained in parent and child conversations and the speech act functions. The method used in this research is descriptive qualitative. The data in this study are in the form of speech between mother and child which are heterogeneous and were obtained from Wonogiri, Ngawi, and Kebumen areas. Data collection techniques used include tapping, see proficient engagements, free engages in proficient engagements, records, and note taking techniques. Data were analyzed using Miles & Huberman's theory. The results of this study indicate several illocutionary functions found in mother and child conversation, including to convey / show something, order, praise, convince something, forbid and also cancel.